2021
DOI: 10.3389/fpsyg.2021.702166
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Perception of Disability: A Developmental Perspective

Abstract: Perception of disability is an important construct affecting not only the well-being of individuals with disabilities, but also the moral compass of the society. Negative attitudes toward disability disempower individuals with disabilities and lead to their social exclusion and isolation. By contrast, a healthy society encourages positive attitudes toward individuals with disabilities and promotes social inclusion. The current review explored disability perception in the light of the in-group vs. out-group dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 400 publications
4
49
0
4
Order By: Relevance
“…Oppositely, there can be a certain level of higher social reluctance and lower social acceptance towards these particular cases. Nevertheless, CFTR-carrier pregnant women did not score significantly different results in the Prenatal Psychosocial Profile regarding stress levels, social support, and self-esteem, probably indicating that the acknowledgement of having a child with potential genetic disorders or malformations does not determine significant changes until or after birth, as other studies suggest [ 37 ].…”
Section: Discussionmentioning
confidence: 75%
“…Oppositely, there can be a certain level of higher social reluctance and lower social acceptance towards these particular cases. Nevertheless, CFTR-carrier pregnant women did not score significantly different results in the Prenatal Psychosocial Profile regarding stress levels, social support, and self-esteem, probably indicating that the acknowledgement of having a child with potential genetic disorders or malformations does not determine significant changes until or after birth, as other studies suggest [ 37 ].…”
Section: Discussionmentioning
confidence: 75%
“…Babik and Gardner [ 6 ] explored the factors affecting the perception of disability from a developmental perspective. Their results suggested that, generally, the favorable attitudes toward disability of 3-year-old children become increasingly negative by 7–8 years, with negativity decreasing subsequently.…”
Section: Attitudes Toward Disability: Gender Age and Previous Contactmentioning
confidence: 99%
“…Children’s attitudes toward disability are an essential factor to be explored to implement effective inclusive education programs and disability awareness campaigns aimed at reducing the discrimination and stigma toward people with disabilities [ 1 ], especially because children with disabilities are often subject to prejudice from their peers [ 6 , 7 ]. As previous studies suggested, it is crucial to understand these attitudes for timely, age-appropriate, and successful interventions to minimize stigmatization and social exclusion behaviors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human rights have consistently been a vital issue in the international arena and unlimited efforts have been carried out by nongovernmental organisations and governments globally in safeguarding these rights, regardless of the characteristics that each individual has (Marcinkutė, 2011). However, there are still certain groups of people who experience exclusion due to their special characteristics such as their gender, socio-economic status, culture, religious background and disabilities (Babik & Gardner, 2021;Prattley et al, 2020). Education, which is a basic human right, is made as a tool to fight against the isolation of these people and eradicate discrimination of the weak sectors of the society.…”
Section: Introductionmentioning
confidence: 99%